Seleção de biocontroladores de pseudomonas savastanoi pv. glycinea em soja - Vilasbôas, Fernanda da Silva (2009)
The bacterial blight, caused by Pseudomonas savastanoi pv. glycinea, is one of the most important diseases of soybeans worldwide. However, in temperate climate regions with mild temperatures this disease is more frequent and severe. Control of bacterial blight can be achieved through different control strategies, which may include the use of biocontrol agents such as endophytic and epiphytic bacteria. This research aimed to control Pseudomonas savastanoi pv. glycinea by means of control agents selected from different hosts and plant parts. The in vitro selection revealed 42 potential candidates. Two isolates (UPF035 and UPF096) also reduced incidence of various seed borne fungi. The use of biocontrolers through seed microbiolization or spray application reduced lesion size and intensity of bacterial blight on soybean plants